Maternal And Fetal Outcome Following Severe Anaemia In Pregnancy: Results From Nobel Medical College Teaching Hospital, Biratnagar, Nepal. (Journal of Nobel Medical College, 2013)
Background: anaemia is a major contributor to maternal death in developing countries. Since it reduces resistance to blood loss, death may occur from bleeding associated with normal delivery. Objective: To explore the association between anaemia and maternal and perinatal complications. Study Design: Retrospective cohort study. Materials and Methods: 100 pregnant women admitted for delivery and having severe anaemia were studied and compared with 100 non anaemic women matched for age, parity, and gestational age. Adverse outcomes analysed were: pregnancy induced hypertension, Postpartum haemorrhage hypertension, Abruptio Placenta,, Infection, Maternal Mortality, Low Birth Weight, and Perinatal mortality. Results : Compared to nonexposed women, exposed women had an increased risk of pregnancy induced hypertension with odds ratio of 5.06 . Postpartum haemorrhage, incidence of wound infection,Intermediate care unit admission were statistically significant in exposed group .However there was no significant difference in maternal mortality among study group.APGAR score